Examining the Impact of Civil Society Organizations on Mother Tongue Education in Cameroon Multilingual Context: Obstacles and Potential Outlooks (Global Journal of Human-Social Science, 2024)
In the multilingual setting of Cameroon, this article looks at the influence of civil society organizations (CSOs) on mother tongue education. The preservation and advancement of mother tongue education are essential for maintaining cultural identity and advancing education in a nation where multiple languages are spoken. However, there are a number of barriers that prevent mother-tongue education programs from being implemented effectively. This study evaluates the barriers that community-based organizations (CSOs) have while trying to advance mother tongue education and considers possible solutions. This study clarifies the many challenges faced by CSOs through a thorough literature review and qualitative research techniques like document analysis and interviews. Language variety, a lack of government backing, scarce resources, and insufficient teacher preparation are some of these challenges.
Keywords: civil society organizations; mother tongue education; cameroon; multilingual context; obstacles